The other side of the coin: systemic effects of Serendipita indica root colonization on development of sedentary plant–parasitic nematodes in Arabidopsis thaliana - Michael W. Opitz; Fernando Evaristo Díaz-Manzano; Virginia Ruiz-Ferrer; Roshanak Daneshkhah; Roland Ludwig; Cindy Lorenz; Carolina Escobar; Siegrid Steinkellner; Krzysztof Wieczorek (Planta, 2024)
Main conclusion Upon systemic S. indica colonization in split-root system cyst and root-knot nematodes benefit from endophyte-triggered carbon allocation and altered defense responses what significantly facilitates their development in A. thaliana . Abstract Serendipita indica is an endophytic fungus that establishes mutualistic relationships with different plants including Arabidopsis thaliana . It enhances host’s growth and resistance to different abiotic and biotic stresses such as infestation by the cyst nematode Heterodera schachtii (CN). In this work, we show that S. indica also triggers similar direct reduction in development of the root-knot nematode Meloidogyne javanica (RKN) in A. thaliana . Further, to mimick the natural situation occurring frequently in soil where roots are unequally colonized by endophytes we used an in vitro split-root system with one half of A. thaliana root inoculated with S. indica and the other half infected with CN or RKN, respectively. Interestingly, in contrast to direct effects, systemic effects led to an increase in number of both nematodes. To elucidate this phenomenon, we focused on sugar metabolism and defense responses in systemic non-colonized roots of plants colonized by S. indica . We analyzed the expression of several SUSs and INVs as well as defense-related genes and measured sugar pools. The results show a significant downregulation of PDF1.2 as well as slightly increased sucrose levels in the non-colonized half of the root in three-chamber dish. Thus, we speculate that, in contrast to direct effects, both nematode species benefit from endophyte-triggered carbon allocation and altered defense responses in the systemic part of the root, which promotes their development. With this work, we highlight the complexity of this multilayered tripartite relationship and deliver new insights into sugar metabolism and plant defense responses during S. indica –nematode–plant interaction.

Serendipita indica changes host sugar and defense status in Arabidopsis thaliana: cooperation or exploitation? - Michael W. Opitz; Roshanak Daneshkhah; Cindy Lorenz; Roland Ludwig; Siegrid Steinkellner; Krzysztof Wieczorek (Planta, 2021)
Main conclusion Manipulation of sugar metabolism upon S. indica root colonization triggers changes in sugar pools and defense responses in A. thaliana . Abstract Serendipita indica is an endophytic fungus that establishes mutualistic relationships with many different plants including important crops as well as the model plant A. thaliana . Successful root colonization typically results in growth promotion and enhanced tolerance against various biotic and abiotic stresses. The fungus delivers phosphorus to the host and receives in exchange carbohydrates. There are hints that S. indica prefers hexoses, glucose, and fructose, products of saccharose cleavage driven by invertases (INVs) and sucrose synthases (SUSs). Carbohydrate metabolism in this interaction, however, remains still widely unexplored. Therefore, in this work, the sugar pools as well as the expression of SUS s and cytosolic INVs in plants colonized by S. indica were analyzed. Using sus1/2/3/4 and cinv1/2 mutants the importance of these genes for the induction of growth promotion and proper root colonization was demonstrated. Furthermore, the expression of several defense-related marker genes in both multiple mutants in comparison to the wild-type plants was determined. Our results show that in colonized A. thaliana plants S. indica manipulates the sugar metabolism by altering the expression of host’s INV and SUS and modulates both the sugar pools and plant defense in its favor. We conclude that the interaction A. thaliana – S. indica is a balancing act between cooperation and exploitation, in which sugar metabolism plays a crucial role. Small changes in this mechanism can lead to severe disruption resulting in the lack of growth promotion or altered colonization rate.

Does iron reduction control the release of dissolved organic carbon and phosphate at catchment scales? Need for a joint research effort - Andreas Musolff; Benny Selle; Olaf Büttner; Michael Opitz; Klaus‐Holger Knorr; Jan H. Fleckenstein; Thorsten Reemtsma; Jörg Tittel (Global Change Biology, 2017)

Unexpected release of phosphate and organic carbon to streams linked to declining nitrogen depositions - Andreas Musolff; Benny Selle; Olaf Büttner; Michael Opitz; Jörg Tittel (Global Change Biology, 2017)
Reductions in emissions have successfully led to a regional decline in atmospheric nitrogen depositions over the past 20 years. By analyzing long‐term data from 110 mountainous streams draining into German drinking water reservoirs, nitrate concentrations indeed declined in the majority of catchments. Furthermore, our meta‐analysis indicates that the declining nitrate levels are linked to the release of dissolved iron to streams likely due to a reductive dissolution of iron( III ) minerals in riparian wetland soils. This dissolution process mobilized adsorbed compounds, such as phosphate, dissolved organic carbon and arsenic, resulting in concentration increases in the streams and higher inputs to receiving drinking water reservoirs. Reductive mobilization was most significant in catchments with stream nitrate concentrations −1 . Here, nitrate, as a competing electron acceptor, was too low in concentration to inhibit microbial iron( III ) reduction. Consequently, observed trends were strongest in forested catchments, where nitrate concentrations were unaffected by agricultural and urban sources and which were therefore sensitive to reductions of atmospheric nitrogen depositions. We conclude that there is strong evidence that the decline in nitrogen deposition toward pre‐industrial conditions lowers the redox buffer in riparian soils, destabilizing formerly fixed problematic compounds, and results in serious implications for water quality.

Reduction of Microcystis blooms in a hypertrophic reservoir by a combined ecotechnological strategy - Thomas Deppe; Klaus Ockenfeld; Andreas Meybohm; Michael Opitz; Jürgen Benndorf (Hydrobiologia, 1999)

Bacteria ingestion by Daphnia galeata in a biomanipulated reservoir: a mechanism stabilizing biomanipulation? - Norbert Kamjunke; Angela Benndorf; Clemens Wilbert; Michael Opitz; Johannes Kranich; Manuela Bollenbach; Jürgen Benndorf (Hydrobiologia, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)